CuS@BSA-NB2 Nanoparticles for HER2-Targeted Photothermal Therapy - Ying, Ming; Li, Qin; Wu, Jingbo; Jiang, Yihang; Xu, Zhourui; Ma, Mingze; Xu, Gaixia (Frontiers in pharmacology, 2022)
Breast cancer is characterized by the uncontrolled proliferation of breast epithelial cells under the action of a variety of carcinogens. Although HER2-inhibitors were currently applied for HER2-positive breast cancer patients, they didn’t work for patients with resistance to HER2-targeted anti-cancer drugs. In this work, we prepared novel CuS@BSA-NB2 nanoparticles (NPs) for breast cancer photothermal therapy (PTT). The NPs had good biocompatibility due to the Bovine Serum Albumin (BSA) encapsulating and excellent targeting to HER2 because of nanobody 2 (NB2). Under 808 nm laser irradiation, CuS@BSA-NB2 NPs had high photothermal conversion efficiency and photothermal stability. Meanwhile, we constructed a stable cell line of MDA-MB-231/HER2 with a high expression of HER2 protein. Immunofluorescence and ICP-MS assays showed that CuS@BSA-NB2 NPs can be specifically enriched and be ingested in MDA-MB-231/HER2 cells. Furthermore, CuS@BSA-NB2 NPs had shown a more significant photothermal treatment effect than CuS@BSA under certain treatment conditions for MDA-MB-231/HER2. In addition, the cytotoxicity assay demonstrated that CuS@BSA-NB2 NPs had a low toxicity for MDA-MB-231/HER2 cells. The above results suggested that CuS@BSA-NB2 NPs were great photothermal therapeutic agents to reduce the malignant proliferation of breast epithelial cells and have potential for breast cancer therapy.